Influence of age and gender on knee and hip isometric strength of recreational physically active young and middle-aged subjects - Gustavo Leporace; Eliane Celina Guadagnin; Liszt Palmeira de Oliveira; Gabriel Zeitoune; Tainá Oliveira; Leonardo Metsavaht (Universidade de São Paulo, 2023)
ABSTRACT Muscle strength is an essential part of the functional assessment of health professionals to select and analyze the effects of clinical interventions. This study aimed to determine the influence of gender and age on isometric strength of hip and knee muscle groups. A total of 127 subjects (50.4% men), aged from 20 to 49 years (stratified into three groups: 20-29 years; 30-39 years; and 40-49 years) participated in this study. A hand-held dynamometer was used to measure isometric normalized torque of the hip abductors, hip external rotators, knee extensors, and knee flexors muscles. Regressions and a two-way analysis of variance were used to identify the influence of age and gender on torque of each muscle group. Age and gender were included in the regression model for all groups. Generally, men aged 20-29 and 30-39 were stronger than age-paired women. For participants aged 40-49, torque was similar for men and women for all muscle groups. There was no difference among age groups for women. Generally, young men were stronger than older men. The association between age and gender in hip and knee strength was proved and liable of subgroup stratification after measurements with a hand-held isometric dynamometer.